Manajemen Travel Ikhwanul Ikhlas Wisata dalam Rekutmen dan Pembinaan Jamaah Umroh di Kota Medan - Fauzan Azmi; Farhan Indra (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to analyze the management of Ikhwanul Ikhlas Wisata Travel in Medan in terms of pilgrim recruitment processes, manasik guidance patterns, assistance systems in the Holy Land, as well as indicators and evaluation of customer satisfaction. The background of this study is based on the increasing competition among Umrah travel agencies, which requires professional, transparent, and customer-oriented services to build trust and loyalty. In this context, Ikhwanul Ikhlas Wisata becomes an interesting case due to its consistency in guiding pilgrims from the initial stage to post-return.This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with three key informants representing management, the company director, and marketing personnel. Data analysis was conducted through data reduction, data display, and conclusion drawing to obtain a comprehensive understanding of Umrah travel management practices.The findings reveal that Ikhwanul Ikhlas Wisata implements a recruitment system that emphasizes transparency in package information, costs, facilities, and departure schedules. Manasik guidance is conducted through both theoretical and practical sessions on a regular basis and supported by competent tour leaders and mutawwif. Customer satisfaction is measured through indicators such as repeat participation, recommendations to family or relatives, and post-return testimonials. The evaluation of satisfaction is utilized as a foundation for continuous improvement in recruitment strategies, guidance patterns, and service quality.